2008
DOI: 10.1086/592083
|View full text |Cite
|
Sign up to set email alerts
|

The Reddest DR3 SDSS/XMM‐NewtonQuasars

Abstract: We have cross-correlated the SDSS DR3 Schneider et al. (2005) quasar catalog with the XMM-Newton archive. Color and redshift selections (g − r ≥ 0.5 and 0.9 < z < 2.1) result in a sample of 17 red, moderate redshift quasars. The redshift selection minimizes possible contamination due to host galaxy emission and Lyα forest absorption. Both optical and X-ray information are required to distinguish between the two likely remaining causes of the red colors: 1) dust-reddening and 2) an intrinsically red continuum. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 83 publications
(130 reference statements)
0
26
0
Order By: Relevance
“…Wilkes et al (2002) and Rose et al (2013) suggested that the red J − K colors (J − K > 2) of red quasars come from a moderate viewing angle in the unification model when the photons from the accretion disk and the BLR are blocked by the dust torus and not by the dust in host galaxies. Other studies suggest that some (∼40%; Young et al 2008) red quasars have intrinsically red continuum (Puchnarewicz & Mason 1998;Whiting et al 2001;Young et al 2008;Rose et al 2013;Ruiz et al 2014) or an unusual covering factor of hot dust (Rose 2014). Also a synchrotron emission peak at NIR wavelength from radio jet (Whiting et al 2001) has been proposed as a possible reason for the intrinsically red continuum of red quasars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilkes et al (2002) and Rose et al (2013) suggested that the red J − K colors (J − K > 2) of red quasars come from a moderate viewing angle in the unification model when the photons from the accretion disk and the BLR are blocked by the dust torus and not by the dust in host galaxies. Other studies suggest that some (∼40%; Young et al 2008) red quasars have intrinsically red continuum (Puchnarewicz & Mason 1998;Whiting et al 2001;Young et al 2008;Rose et al 2013;Ruiz et al 2014) or an unusual covering factor of hot dust (Rose 2014). Also a synchrotron emission peak at NIR wavelength from radio jet (Whiting et al 2001) has been proposed as a possible reason for the intrinsically red continuum of red quasars.…”
Section: Introductionmentioning
confidence: 99%
“…However, our knowledge about quasars is still incomplete, especially with a population of quasars called red quasars, which have been identified in recent infrared surveys Full Table A.1 is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/610/A31 (Webster et al 1995;Benn et al 1998;Cutri et al 2001;Glikman et al 2007Glikman et al , 2012Glikman et al , 2013Urrutia et al 2009;Banerji et al 2012;Stern et al 2012;Assef et al 2013;Fynbo et al 2013;Lacy et al 2013). Red quasars typically indicate quasars with red continua from UV or optical through NIR (e.g., r − K > 5 mag and J − K > 1.3 mag in Urrutia et al 2009; g − r > 0.5 in Young et al 2008), red mid-infrared (MIR) colors (Lacy et al 2004), or detections in X-rays while being obscured in UV and optical wavelengths (Norman et al 2002;Anderson et al 2003;Risaliti & Elvis 2005;Young et al 2009;Brusa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of possible reasons for the red colours of rQSOs, such as intrinsically cooler accretion discs, host galaxy light, or Doppler-boosted synchrotron emission (e.g. Benn et al 1998;Francis et al 2001;Young, Elvis & Risaliti 2008), but the vast majority of luminous rQSOs are reddened by intervening dust (Richards et al 2003;Glikman et al 2004Glikman et al , 2012Rose et al 2013;Kim & Im 2018;Klindt et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For many of these types of sources, there is an ongoing debate about whether (some of) these red QSOs are obscured by either dust or an intrinsically red continuum (Richards et al 2003;Young et al 2008). Thus, our multiband template fit takes into account the possibility of intrinsic dust obscuration within the source.…”
Section: Extinctionmentioning
confidence: 99%